2010
DOI: 10.1038/nature08823
|View full text |Cite
|
Sign up to set email alerts
|

The next generation of scenarios for climate change research and assessment

Abstract: Advances in the science and observation of climate change are providing a clearer understanding of the inherent variability of Earth's climate system and its likely response to human and natural influences. The implications of climate change for the environment and society will depend not only on the response of the Earth system to changes in radiative forcings, but also on how humankind responds through changes in technology, economies, lifestyle and policy. Extensive uncertainties exist in future forcings of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
3,735
2
75

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 5,693 publications
(4,046 citation statements)
references
References 36 publications
26
3,735
2
75
Order By: Relevance
“…For each model we use the ‘historical’ simulations, which are forced with observed aerosol and greenhouse gas concentrations from 1850–2005, and 21st century simulations generated using high emissions Representative Concentration Pathway (RCP8.5; Moss et al , 2010). Monthly precipitation, pressure level zonal wind (U‐wind) and SST output fields from both of these experiments are used and only the first member of the ensemble simulations is utilized in order to provide consistent statistics across models.…”
Section: Data and Methodsologymentioning
confidence: 99%
“…For each model we use the ‘historical’ simulations, which are forced with observed aerosol and greenhouse gas concentrations from 1850–2005, and 21st century simulations generated using high emissions Representative Concentration Pathway (RCP8.5; Moss et al , 2010). Monthly precipitation, pressure level zonal wind (U‐wind) and SST output fields from both of these experiments are used and only the first member of the ensemble simulations is utilized in order to provide consistent statistics across models.…”
Section: Data and Methodsologymentioning
confidence: 99%
“…Recently, Bilbao et al (2015) identified a scenario-independent sea level * Supplemental information related to this paper is available at the Journals Online website: http://dx.doi.org/10.1175/JCLI-D-15-0376.s1. pattern in response to increasing anthropogenic forcings in sea level projections for the twenty-first century, valid for all representative concentration pathway (RCP) scenarios (Moss et al 2010). These forced patterns are partly masked by the internal climate variability, which has a larger influence at regional scales than on the global scale (Hu and Deser 2013;Monselesan et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In the Fifth Assessment Report even more comprehensive scenarios are developed that do not only include changes in radiative forcings, but also the implications of various responses of mankind in terms of technology, mitigation, and adaptation [13].The IPCC uses several climate models. They are yielding widely different results, and come in a rough spatial resolution.…”
Section: Biotic and Abiotic Drivers Call For An Adaptation Of Forestmentioning
confidence: 99%